Secondary students in Selangor's perspectives on constructivist learning environments: preferences versus reality - Ibrahim, Hasniza; Kamarulzaman, Wirawani (Asian Scholar Network, 2024)
In the dynamic educational setting of Malaysia, the shift towards constructivist learning environments represents a crucial change in teaching methodologies. This research delves into the intricacies of constructivist learning environments, particularly within the realm of mathematics education for secondary school students in Selangor. The study aims to unravel distinctions between students preferred and actual experiences within these contructivist educational settings. The specific objectives include: 1) examining the gap between students' perceptions of their preferred and actual constructivist learning environment (CLE), 2) identifying gender differences in preferences for CLE, and 3) determining gender variations in perceptions of actual CLE. Quantitative analysis of students' perspectives reveals a significant misalignment between their preferences and actual encounters within constructivist learning environments. Despite students' inclination towards such environments, the practical implementation falls short of their expectations. Exploring gender differences, the study finds that, while there is no notable gender distinction in preferred constructivist learning environments, male students perceive a higher frequency of constructivist learning in actual experiences compared to their female counterparts. These identified disparities between preferred and actual constructivist learning environments highlight a critical gap in the Malaysian educational landscape. The study advocates for an enhanced implementation of constructivist methodologies, aligning with scholarly calls to address observed discrepancies. The findings offer valuable insights for policymakers and educators to consider in the creation of inclusive and effective learning environments. This research significantly contributes to the ongoing discourse on constructivist learning environments in Malaysia, providing guidance for impactful modifications in educational methodologies.